Complementarity of statistical treatments to reconstruct worldwide routes of invasion: the case of the Asian ladybird Harmonia axyridis - Eric Lombaert; Thomas Guillemaud; Jonathan Lundgren; Robert Koch; Benoît Facon; Audrey Grez; Antoon Loomans; Thibaut Malausa; Oldrich Nedved; Emma Rhule; Arnstein Staverlokk; Tove Steenberg; et al. (Molecular Ecology, 2014)
Inferences about introduction histories of invasive species remain challenging because of the stochastic demographic processes involved. Approximate Bayesian computation ( ABC ) can help to overcome these problems, but such method requires a prior understanding of population structure over the study area, necessitating the use of alternative methods and an intense sampling design. In this study, we made inferences about the worldwide invasion history of the ladybird Harmonia axyridis by various population genetics statistical methods, using a large set of sampling sites distributed over most of the species’ native and invaded areas. We evaluated the complementarity of the statistical methods and the consequences of using different sets of site samples for ABC inferences. We found that the H. axyridis invasion has involved two bridgehead invasive populations in North America, which have served as the source populations for at least six independent introductions into other continents. We also identified several situations of genetic admixture between differentiated sources. Our results highlight the importance of coupling ABC methods with more traditional statistical approaches. We found that the choice of site samples could affect the conclusions of ABC analyses comparing possible scenarios. Approaches involving independent ABC analyses on several sample sets constitute a sensible solution, complementary to standard quality controls based on the analysis of pseudo‐observed data sets, to minimize erroneous conclusions. This study provides biologists without expertise in this area with detailed methodological and conceptual guidelines for making inferences about invasion routes when dealing with a large number of sampling sites and complex population genetic structures.

Living with the enemy: parasites and pathogens of the ladybird Harmonia axyridis - Helen E. Roy; Emma Rhule; Susanne Harding; Lori-Jayne Lawson Handley; Remy L. Poland; Eric W. Riddick; Tove Steenberg (BioControl, 2011)